2016
DOI: 10.1111/iej.12585
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific function and regulation of Osterix in tooth root formation

Abstract: Congenital diseases of tooth roots, in terms of developmental abnormalities of short and thin root phenotypes, can lead to loss of teeth. A more complete understanding of the genetic molecular pathways and biological processes controlling tooth root formation is required. Recent studies have revealed that Osterix (Osx), a key mesenchymal transcriptional factor participating in both the processes of osteogenesis and odontogenesis, plays a vital role underlying the mechanisms of developmental differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 54 publications
(134 reference statements)
1
27
0
Order By: Relevance
“…Later at postnatal stages, when the root is already developed but still elongating, Runx2 expression declines while Osx expression continues to be present in the alveolar bone and in the dental pulp. 20 These findings would account for the results in the present study, in which Osx expression was identified in the osteoblast cells of the alveolar bone and in the odontoblast cells of the pulp dentinal zone of the molar teeth of the posterior samples of the mandibles treated with all decalcification methods. Interestingly, within the same samples, no Runx2 expression was visible regardless of decalcification treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Later at postnatal stages, when the root is already developed but still elongating, Runx2 expression declines while Osx expression continues to be present in the alveolar bone and in the dental pulp. 20 These findings would account for the results in the present study, in which Osx expression was identified in the osteoblast cells of the alveolar bone and in the odontoblast cells of the pulp dentinal zone of the molar teeth of the posterior samples of the mandibles treated with all decalcification methods. Interestingly, within the same samples, no Runx2 expression was visible regardless of decalcification treatment.…”
Section: Discussionsupporting
confidence: 81%
“…This suggests that Osx contributes to MD regression. Osx has wellestablished roles in osteoblast, odontoblast, and cementoblast differentiation (16,24). However, this is evidence for Osx function in sex differentiation.…”
Section: Transcriptome Analysis Identifies Candidate Genes Up-regulatmentioning
confidence: 99%
“…This suggests that Osx contributes to MD regression. Osx has well-established roles in osteoblast, odontoblasts, and cementoblasts differentiation (16,24). However, this is the first evidence for Osx function in sex differentiation.…”
Section: Regression Is Delayed In Osx Null Male Micementioning
confidence: 76%